Ocular care for unconscious patient in ICU (Bangladesh Critical Care Journal, 2023)
Patient requiring ICU support may be conscious or unconscious. Unconscious person has no control upon him orherself or environment. Patients who have much chance for recovery from their illness should be monitored forapparently minor disabilities or ICU related opportunistic diseases. It is also applicable for an unconsciousness state.In ICU 24-hours special health care to be provided with trained person. Extended stay in an ICU is one of the majorissues for development of ocular problems. Lac of eye care facilities or negligence or ignorance, prevents earlydetection. The key to the treatment in ICU is understanding of the underlying pathophysiology of general and ocularproblems.Bangladesh Crit Care J March 2023; 11 (1): 31-35